Endovascular Therapy of 500 Small Asymptomatic Unruptured Intracranial Aneurysms - Oishi, H.; Yamamoto, M.; Shimizu, T.; Yoshida, K.; Arai, H. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: Although the natural course of UIAs remains unclear, the risk of aneurysmal SAH due to small (<10 mm) asymptomatic UIAs is low. Endovascular therapy for UIAs has increased because of device development and the need for less invasive treatment. We report the results, safety, and efficacy of endovascular therapy of small asymptomatic UIAs. MATERIALS AND METHODS: A total of 457 patients with 500 small asymptomatic UIAs (maximum diameter < 10 mm) underwent endosaccular coil embolization at Juntendo University Hospital and affiliated hospitals. We retrospectively evaluated the technical feasibility, immediate and short-to-midterm follow-up anatomic results, procedure-related complications, and clinical outcomes. RESULTS: Endosaccular coil embolization was completed in 481 aneurysms (96.2%) and attempted in 19 (3.8%). Completed aneurysms were treated with the simple (39.5%), balloon-assisted (51.4%), and double-catheter (9.1%) techniques. Immediate angiographic outcomes were CO for 309 (64.2%) aneurysms, RN for 72 (15.0%), and RA for 100 (20.8%). Procedure-related complications occurred in 38 aneurysms (7.6%): 19 ischemic, 11 hemorrhagic, and 8 others. Permanent morbidity and mortality were 0.8% and 0.2%, respectively. Anatomic outcome of 427 aneurysms followed up for >6 months with conventional catheter or MR angiographies showed recanalization in 72 (16.9%) aneurysms, necessitating retreatment in 9.9% (mean, 31.4 months). No patients had aneurysmal SAH during the clinical follow-up period (mean, 34.7 months). CONCLUSIONS: In this series, endovascular therapy of small asymptomatic UIAs was highly feasible with low morbidity and mortality rates. ACAanterior cerebral arteryAChoAanterior choroid arteryAcomAanterior communicating arteryATENAAnalysis of Treatment by Endovascular approach of Nonruptured AneurysmsBAbasilar arteryCOcomplete occlusionD/Ndome-to-neckGDCGuglielmi detachable coilISUIAInternational Study of Unruptured Intracranial AneurysmsmRSmodified Rankin ScalePcomAposterior communicating arteryRAresidual aneurysmRNresidual neckUIAunruptured intracranial aneurysm